The renal function in men with hypertension in conditions of purine and carbohydrate metabolism disorders - O. V. Dudko; M. Yu. Kolesnyk (Zaporozhye State Medical University, 2022)
Aim. To assess the condition of renal function in hypertensive men in conditions of disorders of purine and carbohydrate metabolism Material and methods. 60 male patients (aged from 18 to 65 years) with stage I-II of arterial hypertension (AH) and purine and carbohydrate metabolism disorders were examined. In these patients, the level of uric acid (UA) in daily urine, fractional excretion of UA, creatinine in daily urine, microalbumin in urine and the cystatin C level were determined. Hemodynamics was studied by daily blood pressure monitoring. Assessment of kinetics and deformation of the myocardium in offline mode using the Xstrain software package integrated into the ultrasound device (Esaote, Italy) was made. Patients were divided into 2 clinical groups - 1 group of AH with hyperuricemia, 2 - AH without uricemia. Statistical analysis of the results was performed using the Statistica 13.0 software package (Statsoft, USA). Results. Correlation analysis in group 1 showed a positive correlation of cystatin C with the average daytime systolic blood pressure (SBP) (r = 0.408) and the variability of diastolic blood pressure (DBP) at night (r = 0.405), urinary microalbumin with the average SBP at night (r = 0.390) and average pulse blood pressure (r = 0.402), LV posterior wall thickness (r = 0.438), LV myocardial mass index (r = 0.621), end-diastolic index (EDI) (r = 0.492), end-systolic index (ESI) (r = 0.426), LV anterior-posterior size (r = 0.385). A negative correlation was established between blood serum SC and ejection fraction (EF) of the LV (r = -0.410), urinary microalbumin with cardiac index (SI) (r = -0.555) and the speed of movement of the lateral (e' lat) part of the annulus fibrosus mitral valve (r = -0.453). Conclusions. As a result of the studies, the negative influence of hyperuricemia and hyperglycemia in patients with AH on renal function was established. These changes were evidenced by an increase in microalbuminuria level, a decrease in the fractional excretion of UA, an increasing the serum UA level, remodeling of the myocardium, and worsening of the heart systolic function, worsening of the daily blood pressure profile.